Peningkatan Hasil Belajar IPAS Menggunakan Model Project Based Learning di Kelas V SDN 10 Koto Baru Kabupaten Solok - Sasa, Salsabila Idha Putri; Astimar, Nelly (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the improvement in student learning outcomes using the Project-Based Learning model in IPAS learning in grade V of SDN 10 Koto Baru, Solok Regency. This study is a Classroom Action Research (CAR) using a mixed method approach conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of this study were the teacher and 12 students in Grade V at SDN 10 Koto Baru, Solok Regency, during the January-June semester of the 2024/2025 academic year. The research data consisted of observations of teaching modules, observations of teacher and student activities, and student learning outcomes using the Project-Based Learning model. Data collection techniques included observation analysis, tests, and non-tests. The results of the teaching module planning observation in Cycle I were 91.67% (B), increasing to 95.83% (SB) in Cycle II. The results of teacher observation in Cycle I were 88.75% (B), increasing to 93.33% (SB) in Cycle II. The results of student observation in Cycle I were 88.75% (B), increasing to 93.33% (SB) in Cycle II. Student learning outcomes in Cycle I were 72.3 (K), increasing to 83.07 (B) in Cycle II. Thus, the study shows that the Project-Based Learning model can improve student learning outcomes in IPAS learning in Grade V at SDN 10 Koto Baru, Solok Regency.